160k views
0 votes
Y = - x - 6
y = x - 4​

User TomJ
by
6.6k points

1 Answer

1 vote

For this case we have a system of two equations with two variables:


y = -x-6\\y = x-4

Equaling the equations we have:


-x-6 = x-4

Adding x to both sides of the equation we have:


-6 = x + x-4\\-6 = 2x-4

Adding 4 to both sides of the equation we have:


-6 + 4 = 2x\\-2 = 2x

Dividing 2 on both sides of the equation we have:


x = \frac {-2} {2}\\x = -1

We find the value of the variable y:


y = x-4 = -1-4 = -5

Thus, the system solution is:


(x, y): (- 1, -5)

Answer:


(x, y): (- 1, -5)

User Rjdmello
by
6.7k points